2014
DOI: 10.1111/aji.12321
|View full text |Cite
|
Sign up to set email alerts
|

Association between Plasminogen Activator Inhibitor‐1 Gene Polymorphisms and Recurrent Pregnancy Loss: A Systematic Review and Meta‐Analysis

Abstract: Human plasminogen activator inhibitor-1 (PAI-1) is closely related to embryonic development and pregnancy success. The association between PAI-1 gene polymorphisms (PAI-1-844G/A and PAI-1-675G/A) and the risk of recurrent pregnancy loss (RPL) is controversial. Therefore, we perform this review to clarify the association between PAI-1 gene polymorphisms and RPL risk. We performed a systematic search for studies that described the effect of PAI-1 polymorphisms on RPL risk. The odds ratios (ORs) with correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 39 publications
1
28
0
3
Order By: Relevance
“…We found that the PAI-1 4G/5G genotype was more frequent in the group of women with 1 SM (56%) versus the control group (42%). Our results are similar to the results of a meta-analysis by Chen et al [16] which confirmed that PAI-1 4G/5G polymorphisms play a potential role in SMs, indicating that the PAI-1 4G/5G polymorphism is significantly associated with a risk of SM (OR = 1.70, 95% CI 1.21-2.38). Results of another meta-analysis conducted by Xuejiao et al [17] suggest that the PAI-1 4G/5G polymorphism might be associated with SM development specifically in Caucasians (OR = 2.23, 95% CI 1.44-3.46).…”
Section: Discussionsupporting
confidence: 92%
“…We found that the PAI-1 4G/5G genotype was more frequent in the group of women with 1 SM (56%) versus the control group (42%). Our results are similar to the results of a meta-analysis by Chen et al [16] which confirmed that PAI-1 4G/5G polymorphisms play a potential role in SMs, indicating that the PAI-1 4G/5G polymorphism is significantly associated with a risk of SM (OR = 1.70, 95% CI 1.21-2.38). Results of another meta-analysis conducted by Xuejiao et al [17] suggest that the PAI-1 4G/5G polymorphism might be associated with SM development specifically in Caucasians (OR = 2.23, 95% CI 1.44-3.46).…”
Section: Discussionsupporting
confidence: 92%
“…In 1984, Wiman et al was the first to characterize the association between increased PAI-1 levels and preeclampsia [8]. A meta-analysis of 6 case control studies investigating the 4G/5G polymorphism found no significant difference in the frequency of the 4G allele in patients with and without preeclampsia; however, patients with the 4G allele had a 1.27-fold increased risk of preeclampsia [7,8]. Similarly, a meta-analysis of 18 case control studies found that the 4G/5G polymorphism is associated with an increased risk of RPL (OR = 1:7, 95%CI = 1:21 − 2:38), and advocated for PAI-1 screening and treatment with anticoagulation [7].…”
Section: Discussionmentioning
confidence: 99%
“…The PAI-1 gene promoter region has well-characterized polymorphisms, specifically the 4G insertion/5G deletion polymorphism, which enhances transcription of PAI-1 [7,8]. The expression of PAI-1 is modified by atherosclerotic risk factors that induce endothelial damage, including diabetes, insulin resistance, and hypertriglyceridemia [8].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with the previous reports, which demonstrated an increased incidence of the 4G allele and/or 4G/4G genotype among the patients with RPL, although contradictory results were reported . Recently, two meta‐analysis of PAI‐1 gene mutation in women with RPL have published, which demonstrated an association between PAI‐1 4G/5G polymorphism and RPL . However, another meta‐analysis failed to demonstrate an association, possibly due to the high heterogeneity among the study population, such as ethnicity, number of abortions considered as RPL, and the exclusion criteria of study population with known causes of RPL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found an association between PAI‐1 ‐675 4G/5G polymorphism and RPL and to a lesser extent, RIF . In this study, we aim to investigate the association between PAI‐1 4G/5G polymorphism with various types of reproductive failures and compare the metabolic, hormonal, and immune profiles of these patients in association with PAI‐1 genotypes.…”
Section: Introductionmentioning
confidence: 99%